Social networking and youth - Quintanilla Paulet, María Francisca (2015)
In this article, the author presents the fruits of his research on the relationship between the virtualworld and youth. The challenge of the new environment is presented here with a review from thepsychological, social and educational dimensions. The possible consequences of the misuse, aswell as the opportunities that this new situation leads, are also shown. Finally, recomendationsto take account both by parents and by educators are suggested.